Consumers’ attitudes towards western and asian celebrity endorsement in cosmetics industry - Annie Tan Wee Wen (2011)
Celebrities are increasingly being employed by cosmetics companies to market their products in the market in order to boost up sales. This study analyzes Malaysian female consumers’ perception towards Asian celebrity endorsers and Western celebrity endorsers. Findings suggested that both celebrity endorsements influence Malaysian female consumers but Asian celebrity endorsers’ influence is to a greater degree. The results from a survey conducted on 100 Malaysian female respondents provide insight into how consumers’ perceptions differ between the celebrity endorsers.